Peran dan Aktivitas Perempuan Era Muhammad SAW (Studi Atas Hadis-Hadis Riwayat Sahabat Perempuan) - Zunly Nadia (HUMANISMA : Journal of Gender Studies, 2020)
This paper shows how the role of women both in the public and domestic area in the era of phrophet Mohamamd. In this case, the paper focus on woman companion transmitter who are directly wrapped up in the missionary work with the prophet. In addition, the paper will show the relation between woman companion transmitter activity and their hadis transmission, under assumtion that the role of woman will influence to the hadis texts which are transmitted. This because, as a text, hadis was transmitted in the certain context and condition. Accordingly, every transmitter had different hadis transmission based on his/her context, status,  profession, and even gender construction. This is why, the paper will write the woman companion transmitter who play their role and their activity influence their hadis transmission.